The Relationship between Work Shifts and Work Environment with Nurse Fatigue in the Emergency Department - Nadya Putri Dewanti; Nusavia Astra Jingga; Y. Denny A. Wahyudiono (The Indonesian Journal of Occupational Safety and Health, 2022)
Introduction: Work fatigue is one of the common health problems faced by nurses. Work shifts and work environment are factors that cause work fatigue for nurses. Nurse fatigue can cause work accidents and decreased work productivity. It was reported that 47% of employees experienced decreased productivity, and 32% of employees experienced injuries and near misses due to work fatigue. This research aimed to figure out whether and to what extent work shifts and work environment were correlated with nurse fatigue at the emergency department of Surabaya Haji General Hospital. Method: This analytic observational study employed a cross-sectional approach with work fatigue as the dependent variable and work shifts and work environment as independent variables. This research used the Spearman’s correlation test with 30 emergency department nurses at Surabaya Haji General Hospital as the samples. The instruments used in this research were work environment questionnaires and work fatigue questionnaires from IFRC. Results: The results showed that work shift had a very weak relationship with work fatigue. At the same time, there was a moderate relationship between work environment and work fatigue. Conclusion: The work fatigue among emergency department nurses at the Surabaya Haji General Hospital observed had a very weak relationship with work shifts and a moderate relationship with their work environment.